Graphite for friction material and preparation method and application thereof

By blending carbon materials with organic acids and sulfuric acid, sulfur elements are generated to fill in carbon materials, and combined with fillers and sealing agents, the problem of insufficient oxidation and rebound rate of graphite materials under high temperature environments is solved, and friction materials are improved corrosion resistance and rebound rate.

CN119191285BActive Publication Date: 2025-02-14TANGSHAN KIMWAN SPECIAL CARBON & GRAPHITE COLTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411718117.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing graphite materials oxidize rapidly in high temperature environments, resulting in reduced lubricating performance of friction materials, intensified wear, and insufficient rebound rate, affecting braking performance and driver comfort.

Method used

By blending the carbon material with high concentrations of organic acid and sulfuric acid, the reaction is made to form sulfur element filled in the carbon material, and the rebound rate and density of elastic graphite are increased by the combination of fillers and sealants.

Benefits of technology

The rebound rate and density of graphite used for friction materials is improved, and its corrosion resistance and low density characteristics are enhanced in high temperature environments, meeting the needs of friction materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The present application relates to the technical field of graphite materials, and specifically discloses a graphite for friction material, a preparation method thereof and an application thereof. A graphite for friction material comprises the following raw materials in parts by weight: 10000±20 parts of carbon material, 4900-9900 parts of sulfuric acid, 9900-29700 parts of organic acid, and 60-80 parts of filler; wherein the weight ratio of carbon material, organic acid and sulfuric acid is 1: (0.99-2.97): (0.49-0.99); the carbon material is one of coke-type carbon material or graphite-type carbon material; the filler comprises 24-28 parts of modified iron powder, 12-14 parts of sodium bicarbonate powder and 30-32 parts of sealing agent; the organic acid is one of acetic acid, oxalic acid or citric acid; and the preparation method thereof is: after mixing organic acid and sulfuric acid, adding carbon material, mixing and washing to neutrality, drying, calcining, graphitizing, adding sodium bicarbonate and iron powder and mixing, adding sealing agent and mixing. The graphite for friction material of the present application can be used to prepare friction material, which has the advantage of improving the rebound rate of elastic graphite, thereby meeting the use requirements of friction material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of graphite materials, and more specifically, to graphite for friction materials and a preparation method and application thereof. Background Art

[0002] The most commonly used graphite in friction materials is artificial graphite, which is mainly made by calcining high-quality petroleum coke or asphalt coke at a high temperature of 2500-3000℃. Since adding an appropriate amount of artificial graphite can improve the lubrication properties of friction materials, reduce wear and ease friction, artificial graphite has been widely used in brake materials.

[0003] When the operating temperature is higher than 500℃, graphite will oxidize quickly, making the surface of the friction material loose and causing aggravated wear. Therefore, in an air environment, artificial graphite is suitable for use at medium and low temperatures. When it exceeds 500℃, the lubrication performance decreases. In addition, elastic graphite can reduce the sensitivity of brake pads to speed and temperature, reduce the change in friction coefficient caused by speed and temperature, and help improve braking performance and driver comfort. Therefore, elastic graphite is usually used to replace artificial graphite and added to friction materials, so that the friction pads have the characteristics of high temperature resistance, corrosion resistance, and low density.

[0004] As an important factor affecting the compression and rebound performance of elastic graphite, the rebound rate of elastic graphite currently developed in my country still has a certain gap with that of foreign countries. In order to improve the rebound rate of elastic graphite and reduce the production cost of friction materials, the inventor has developed graphite for friction materials to replace foreign imported materials, thereby meeting the demand for the use of friction materials. Summary of the invention

[0005] In order to improve the rebound rate of elastic graphite and thus meet the use requirements of friction materials, the present application provides graphite for friction materials and a preparation method and application thereof.

[0006] In the first aspect, the present application provides a graphite for friction material, which adopts the following technical solution:

[0007] A graphite for friction material, comprising the following raw materials in parts by weight:

[0008] 10000±20 parts of carbon material, 4900-9900 parts of sulfuric acid, 9900-29700 parts of organic acid, 60-80 parts of filler;

[0009] The weight ratio of carbon material, organic acid and sulfuric acid is 1: (0.99-2.97): (0.49-0.99);

[0010] The carbon material is one of a coke-type carbon material or a graphite-type carbon material;

[0011] The filler comprises 24-28 parts of modified iron powder, 12-14 parts of sodium bicarbonate powder and 30-32 parts of sealing agent;

[0012] The organic acid is one of acetic acid, oxalic acid or citric acid.

[0013] By adopting the above technical scheme, elastic graphite is prepared by blending carbon material with high-concentration organic acid and sulfuric acid, so that sulfuric acid reacts with carbon material and fills sulfur element in carbon material, while organic acid adjusts pH in reaction system, promotes reaction and facilitates separation of generated reaction product and carbon material, reduces possibility of impurity residue in carbon material, after graphitization, sulfur element generates gas and separates from carbon material, so that carbon material forms elastic graphite, filler is filled in pores opened on elastic graphite, at this time, sodium bicarbonate and modified iron powder are located in pores, and sealing agent blocks pore openings, thereby increasing number of closed micropores on elastic graphite, and further increasing resilience of obtained elastic graphite, thereby meeting use requirements of friction material.

[0014] Preferably, the modified iron powder is prepared by wrapping sodium polyacrylate with iron powder, and the weight ratio of the iron powder to sodium polyacrylate is (3-5):1.

[0015] By adopting the above technical scheme, when the weight ratio of iron powder to sodium polyacrylate is within this range, sodium polyacrylate is wrapped on the surface of iron powder, which reduces the possibility of mutual contact and agglomeration between iron powders, improves the dispersibility of iron powder, and when iron powder is filled in the pores of elastic graphite, sodium polyacrylate reduces the possibility of iron powder sedimentation, so that the iron powder is always evenly distributed in the pores; when the ratio of iron powder to sodium polyacrylate is greater than this range, sodium polyacrylate is difficult to fully wrap the iron powder, which may cause the iron powder to be difficult to fully disperse and agglomerate; when the ratio of iron powder to sodium polyacrylate is less than this range, it is easy to cause the possibility of waste of raw materials, which in turn has an adverse effect on production costs.

[0016] Preferably, the sealing agent is prepared by graphene aerogel adsorbing asphalt-based aluminum paste, and the weight ratio of graphene aerogel to asphalt-based aluminum paste is 1: (10-12).

[0017] By adopting the above technical scheme, when graphene aerogel and asphalt-based aluminum paste are physically adsorbed by graphene aerogel, the asphalt-based aluminum paste is evenly dispersed and filled into the pores of elastic graphite. Due to the high elasticity of graphene aerogel itself, the rebound rate of the prepared elastic graphite is improved. When friction material is prepared by elastic graphite, the graphene aerogel squeezes out the internal asphalt-based aluminum paste under hot pressing conditions, which is convenient for sealing the openings of the pores on the elastic graphite, further facilitating the formation of closed micropores on the elastic graphite, thereby improving the rebound rate of the elastic graphite and meeting the use requirements of the friction material.

[0018] Preferably, the preparation method of the sealing agent is:

[0019] Freeze-forming the asphalt-based aluminum slurry to obtain a formed solid;

[0020] The formed solid is crushed to obtain particles;

[0021] The graphene aerogel is added to the prepared particles according to a weight ratio and ultrasonically dispersed to prepare a sealing agent.

[0022] By adopting the above technical scheme, the asphalt-based aluminum paste is freeze-formed and crushed to form a solid with low viscosity that is easy to be physically adsorbed by the graphene aerogel, and the particles of the graphene aerogel and the asphalt-based aluminum paste are fully mixed by ultrasonic dispersion, so that the asphalt-based aluminum paste particles can be filled in the pores of the graphene aerogel, and the asphalt-based aluminum paste can be fully dispersed to fill the pores of the elastic graphite.

[0023] Preferably, the particle size of the sodium bicarbonate powder is 140-160 nm.

[0024] By adopting the above technical solution, when the particle size of the sodium bicarbonate powder is within this range, the sodium bicarbonate powder is easy to fill the pores on the elastic graphite, and when the sodium bicarbonate powder is decomposed by heat, sodium carbonate, carbon dioxide gas and water are generated, which is easy to form micropores on the surface of the sodium bicarbonate, and the sodium carbonate is further decomposed and releases carbon dioxide gas in a heated environment, further forming micropores on the surface of the sodium carbonate, and the generated carbon dioxide gas enters the graphene aerogel, thereby squeezing out the asphalt-based aluminum slurry and sealing the pore openings of the elastic graphite, thereby increasing the number of closed micropores in the elastic graphite, and the generated water reacts with the iron powder in a heated environment. Ferroferric oxide is generated and volume expansion occurs, thereby forming a ferroferric oxide skeleton, which increases the closed micropores inside the elastic graphite and supports the elastic graphite at the same time, reduces the adverse effect on the strength of the elastic graphite, and meets the use requirements of the friction material; when the particle size of the sodium bicarbonate powder is too large, it is easy to cause the sodium bicarbonate powder to be too large and difficult to enter the pores of the elastic graphite; when the particle size of the sodium bicarbonate powder is too small, it is easy to cause the sodium bicarbonate powder to agglomerate and difficult to fully disperse, and then it is easy to cause the agglomerated sodium bicarbonate powder to be difficult to enter the pores of the elastic graphite, thereby causing an adverse effect on the rebound rate of the elastic graphite.

[0025] In a second aspect, the present application provides a method for preparing graphite for friction material, using the following technical solution:

[0026] A method for preparing graphite for friction material comprises the following steps:

[0027] After mixing the organic acid and sulfuric acid according to the weight ratio, add the carbon material and mix at 40-80°C for 20-60 minutes;

[0028] Washing the obtained mixture until it is neutral, and drying it to obtain a dried carbon material;

[0029] The dried carbon material is calcined at 600±10° C. for 12±4 h, and the calcined carbon material is graphitized for 36±1 h to obtain graphitized elastic graphite;

[0030] Mixing sodium bicarbonate powder and modified iron powder according to weight ratio, adding into graphitized elastic graphite and mixing well to prepare a mixture;

[0031] The sealing agent is added into the mixture and mixed evenly to obtain graphite for friction material.

[0032] By adopting the above technical solution, sulfuric acid reacts with the carbon material, and the organic acid adjusts the pH in the reaction system and promotes the reaction, thereby introducing sulfur into the carbon material. After washing, drying, calcining, and graphitization, the sulfur element is converted into sulfur dioxide and dissipated, and the carbon material is converted into elastic graphite. At this time, sodium bicarbonate powder and modified iron powder are mixed and filled into the pores of the elastic graphite. The modified iron powder reduces the possibility of sodium bicarbonate powder sedimentation, thereby making the micropores on the surface of sodium bicarbonate uniformly distributed in the elastic graphite, and the sealing agent is filled into the pores of the elastic graphite and the pore openings are blocked, thereby further increasing the number of closed micropores in the elastic graphite. When the prepared graphite for friction material is applied to friction material, the sealing agent increases the number of closed micropores inside the graphite for friction material, thereby increasing the resilience of the graphite for friction material, and when the prepared friction material is used, the friction material is heated to decompose the sodium bicarbonate, thereby further increasing the number of closed micropores in the friction material, and the iron powder near the sodium bicarbonate in the friction material generates ferrosoferric oxide and expands in volume, thereby improving the strength of the prepared friction material, and the iron powder near the outer surface of the friction material is oxidized to form iron oxide, thereby reducing the possibility of oxidation of other components in the friction material, thereby further meeting the use requirements of the friction material.

[0033] Preferably, the graphitization temperature is 2000-2800°C.

[0034] By adopting the above technical solution, when the graphitization temperature is within this range, as the temperature rises, the graphitization degree of the carbon material gradually increases, which promotes the rearrangement of carbon atoms to form a more ordered graphite structure, and the thermal conductivity and mechanical properties are increased. When the graphitization temperature is lower than this range, it is easy to cause incomplete graphitization, affecting the rebound rate of the graphite used in the friction material; when the graphitization temperature exceeds this range, it is easy to cause the graphite used in the friction material to crack and be damaged, thereby adversely affecting the mechanical properties of the friction material obtained.

[0035] In a third aspect, the present application provides an application of graphite for friction material, using the following technical solution:

[0036] A friction material made of graphite for friction material comprises the following steps:

[0037] The reinforcing fiber, steel fiber, filler, phenolic resin and friction material graphite are mixed evenly, the mixed raw materials are added into a pressing mold, and hot pressing is performed at a hot pressing temperature of 160±10° C. and a pressure of 30±1 MPa to obtain the friction material.

[0038] By adopting the above technical scheme, the prepared graphite for friction material is applied to the friction material by hot pressing, which makes it easy to extrude the asphalt-based aluminum slurry into the graphene aerogel, thereby sealing the pore openings of the graphite for membrane material, improving the rebound rate of the graphite for friction material, and meeting the use requirements of the friction material.

[0039] In summary, this application has the following beneficial effects:

[0040] 1. Fill the filler into the open pores on the elastic graphite. At this time, sodium bicarbonate and iron powder are located in the pores, and the sealing agent blocks the pore openings, thereby increasing the number of closed micropores on the elastic graphite, thereby increasing the rebound rate of the obtained elastic graphite, and thus meeting the use requirements of the friction material.

[0041] 2. By physically adsorbing asphalt-based aluminum paste on graphene aerogel, the asphalt-based aluminum paste can be evenly dispersed and filled into the pores of elastic graphite. Due to the high elasticity of graphene aerogel itself, the rebound rate of the elastic graphite can be improved when graphene aerogel is filled into the pores. When friction materials are prepared by elastic graphite, the graphene aerogel squeezes out the internal asphalt-based aluminum paste under hot pressing conditions, which is convenient for sealing the openings of the pores on the elastic graphite, further facilitating the formation of closed micropores on the elastic graphite, thereby improving the rebound rate of the elastic graphite and meeting the use requirements of the friction materials.

[0042] 3. When the particle size of sodium bicarbonate powder is within this range, the sodium bicarbonate powder is easy to fill the pores on the elastic graphite. When the sodium bicarbonate powder is decomposed by heat, sodium carbonate, carbon dioxide gas and water are generated, which are easy to form micropores on the surface of sodium bicarbonate. Sodium carbonate is further decomposed and releases carbon dioxide gas in a heated environment, further forming micropores on the surface of sodium carbonate, thereby increasing the number of closed micropores in the elastic graphite. The generated water reacts with iron powder in a heated environment to generate ferroferric oxide and expands in volume, thereby forming a ferroferric oxide skeleton, which increases the number of closed micropores inside the elastic graphite while supporting the elastic graphite, reducing the adverse effect on the strength of the elastic graphite and meeting the use requirements of the friction material. DETAILED DESCRIPTION

[0043] The present application is further described in detail below with reference to the embodiments.

[0044] The rebound rate detection method and the initial oxidation temperature detection method in all embodiments and comparative examples are as follows:

[0045] 1. Bounce rate

[0046] Test equipment: Material testing machine capable of applying load evenly and measuring load with an accuracy of ±1%.

[0047] Samples: Take 5 groups of samples, 3 samples in each group.

[0048] Test steps: Load the sample into a mold with an inner diameter of 40 mm until the initial height of the sample in the mold is 8.0 mm (measure three points at equal distances and take the arithmetic average), place a top plug that matches the mold on the upper side of the sample, and place the mold with the upper end sealing plug between the pressure head and the base, so that the load is applied uniformly through the axis of the pressure head to an initial load of 0.35 MPa, maintain for 15 seconds, and record the deformation amount, then uniformly load to 35 MPa within 10 seconds, maintain for 60 seconds, and record the deformation amount under the final load, then unload to the initial load, maintain for 60 seconds, and record the deformation amount.

[0049] Test results and calculations:

[0050]

[0051] Where: R——rebound rate, %;

[0052] ∆t 1 ——deformation under initial load, mm;

[0053] ∆t 2 ——deformation under final load, mm;

[0054] ∆t 3 ——Deformation after unloading to initial load, mm.

[0055] 2. Initial oxidation temperature

[0056] Test equipment:

[0057] Thermal balance: Zero or deflection type. When the sample mass is less than 50 mg, the accuracy is ±0.020 mg. The structure of the thermal balance allows airflow around the sample and transfers heat to the sample at a constant rate.

[0058] Furnace: With low heat capacity shell, it can be heated and cooled quickly or slowly (usually at least 50℃ / min) in the temperature range from room temperature to 1200℃.

[0059] Temperature sensor: measures the sample temperature. Located as close to the sample as possible.

[0060] Temperature program controller: can perform linear rate scans within a predetermined temperature range.

[0061] Recording equipment: Displays the relationship between mass loss and temperature or time, and records changes in sample mass and temperature and / or time.

[0062] Sample dish: It has a shape and size sufficient to hold 10 mg of sample and is made of a material that can withstand the maximum operating temperature.

[0063] Protective gas: dry air with a water content of less than 0.001% (mass fraction).

[0064] Flow meter: Measures gas flow rate in the range of 50mL / min to 150mL / min.

[0065] Balance: Measure the initial mass of the sample with an accuracy of 0.01 mg.

[0066] Sample: Take 5 groups of samples, 10 mg each.

[0067] Sample steps:

[0068] Zero the thermobalance, place the weighed sample in the sample dish, and place the sample dish on the thermobalance, select the gas flow rate, pass the gas flow and record the initial mass. Start the instrument and heat it to 1050℃ at a rate of 100℃ / min.

[0069] Sample results: Thermogravimetric data is displayed in the form of a mass change versus temperature curve to determine the initial oxidation temperature of the sample.

[0070] raw material

[0071] The raw materials used in the preparation examples and embodiments of the present application can be obtained from commercial sources, wherein the concentration of sulfuric acid is 98%, the concentration of organic acid is 99%, and the iron powder, sodium polyacrylate, graphene aerogel and sodium bicarbonate powder are all nano-sized particles.

[0072] Preparation Example

[0073] Preparation Example 1 Modified Iron Powder

[0074] Preparation Example 1.1

[0075] A modified iron powder is prepared by the following steps:

[0076] 75 g of iron powder and 25 g of sodium polyacrylate were mixed to obtain modified iron powder.

[0077] Preparation Example 1.2

[0078] Different from Preparation Example 1.1, in Preparation Example 1.2, the amount of iron powder added is 80 g and the amount of sodium polyacrylate added is 20 g.

[0079] Preparation Example 1.3

[0080] Different from Preparation Example 1.1, the amount of iron powder added in Preparation Example 1.3 is 86 g, and the amount of sodium polyacrylate added is 14 g.

[0081] Preparation Example 1.4

[0082] Different from Preparation Example 1.1, the amount of iron powder added in Preparation Example 1.4 is 50 g, and the amount of sodium polyacrylate added is 50 g.

[0083] Preparation Example 1.5

[0084] Different from Preparation Example 1.1, the amount of iron powder added in Preparation Example 1.5 is 90 g and the amount of sodium polyacrylate added is 10 g.

[0085] Preparation Example 1.6

[0086] Different from Preparation Example 1.2, in Preparation Example 1.6, an equal amount of sodium polyacrylate is replaced by sodium silicate.

[0087] Preparation Example 1.7

[0088] Different from Preparation Example 1.2, in Preparation Example 1.7, an equal amount of sodium polyacrylate is replaced by fumed silica.

[0089] Preparation Example 2 Sealing Agent

[0090] Preparation Example 2.1

[0091] A sealing agent is prepared by the following steps:

[0092] 109 g of asphalt-based aluminum slurry was freeze-formed to obtain a formed solid;

[0093] The formed solid is crushed to obtain particles;

[0094] 11 g of graphene aerogel was added to the prepared particles and ultrasonically dispersed to prepare a sealing agent.

[0095] Preparation Example 2.2

[0096] Different from Preparation Example 2.1, the amount of asphalt-based aluminum paste added in Preparation Example 2.2 is 110 g, and the amount of graphene aerogel added is 10 g.

[0097] Preparation Example 2.3

[0098] Different from Preparation Example 2.1, the amount of asphalt-based aluminum paste added in Preparation Example 2.3 is 111 g, and the amount of graphene aerogel added is 9 g.

[0099] Preparation Example 2.4

[0100] Different from Preparation Example 2.1, the amount of asphalt-based aluminum paste added in Preparation Example 2.4 is 114 g, and the amount of graphene aerogel added is 6 g.

[0101] Preparation Example 2.5

[0102] Different from Preparation Example 2.1, the amount of asphalt-based aluminum paste added in Preparation Example 2.5 is 100 g, and the amount of graphene aerogel added is 20 g.

[0103] Preparation Example 2.6

[0104] Different from Preparation Example 2.2, in Preparation Example 2.6, an equal amount of graphene aerogel is replaced by activated carbon.

[0105] Preparation Example 2.7

[0106] Different from Preparation Example 2.2, in Preparation Example 2.7, the asphalt-based aluminum paste is replaced by an equal amount of silica-alumina resin. Example

[0107] Example 1 Raw material ratio and process parameters

[0108] Example 1.1

[0109] A graphite for friction material is prepared by the following steps:

[0110] After mixing 9900g of acetic acid and 9900g of sulfuric acid, add 10000g of coke and mix at 40°C for 20min;

[0111] Washing the obtained mixture until it is neutral, and drying it to obtain a dried carbon material;

[0112] The dried carbon material is calcined at 600° C. for 12 h, and the calcined carbon material is graphitized at 2000° C. for 36 h to obtain graphitized elastic graphite;

[0113] 12 g of sodium bicarbonate powder with a particle size of 140 nm and 28 g of the modified iron powder from Preparation Example 1.1 were mixed and added to the graphitized elastic graphite and mixed to prepare a mixture;

[0114] 30 g of the sealing agent from Preparation Example 2.1 was added to the mixture and mixed well to obtain graphite for friction material.

[0115] Examples 1.2-1.7

[0116] Different from Example 1.1, the raw material ratios and process parameters in Examples 1.2-1.7 are different, see Table 1 for details.

[0117] Table 1 Raw material ratios and process parameters of Examples 1.1-1.7

[0118]

[0119] Example 1.8

[0120] Different from Example 1.6, in Example 1.8, an equal amount of graphite is used to replace coke.

[0121] Example 1.9

[0122] The difference from Example 1.8 is that in Example 1.9, acetic acid is replaced by an equal amount of oxalic acid.

[0123] Example 1.10

[0124] The difference from Example 1.8 is that in Example 1.10, an equal amount of citric acid is used to replace acetic acid.

[0125] Comparative Example 1

[0126] Different from Example 1.1, in Comparative Example 1, an equal amount of iron powder was used to replace the modified iron powder.

[0127] Comparative Example 2

[0128] Different from Example 1.1, in Comparative Example 2, an equal amount of sodium carbonate powder was used to replace sodium bicarbonate powder.

[0129] Comparative Example 3

[0130] Different from Example 1.1, in Comparative Example 3, an equal amount of calcium carbonate powder was used to replace sodium bicarbonate powder.

[0131] The rebound rate and initial oxidation temperature of the graphite for friction material prepared in Examples 1.1-1.10 and Comparative Examples 1-3 were tested, as shown in Table 2 for details.

[0132] Table 2 Performance test data table

[0133]

[0134] Combining Table 1 and Table 2, it can be seen that the graphite for friction material prepared in Examples 1.1-1.10 performs better than that in Comparative Example 1 in terms of rebound rate and initial oxidation temperature, which indicates that the use of modified iron powder in Examples 1.1-1.10 of the present application is beneficial to improving the rebound rate and initial oxidation temperature of the graphite for friction material prepared.

[0135] Combining Example 1.1 and Comparative Examples 2-3, it was found that in Comparative Example 2, sodium bicarbonate was replaced with an equal amount of sodium carbonate, and the graphite for friction material obtained was worse than that in Example 1.1 in terms of rebound rate and initial oxidation temperature; in Comparative Example 3, sodium bicarbonate was replaced with an equal amount of calcium carbonate, and the graphite for friction material obtained was worse than that in Example 1.1 in terms of rebound rate and initial oxidation temperature, which indicates that the sodium bicarbonate selected in Example 1.1 is beneficial to improving the rebound rate and initial oxidation temperature of the graphite for friction material obtained.

[0136] The effects of the amounts of acetic acid and sulfuric acid added were investigated in Examples 1.1-1.3. The results showed that the graphite for friction material prepared in Example 1.2 performed better in terms of rebound rate and initial oxidation temperature. This may be because the amounts of acetic acid and sulfuric acid added in Example 1.2 promoted the reaction between sulfuric acid and carbon material, thereby filling the carbon material with an appropriate amount of sulfur element, thereby increasing the degree of graphitization of the carbon material and improving the rebound rate of the graphite for friction material prepared.

[0137] Taking Example 1.2 as a control, Examples 1.4-1.5 investigated the effects of mixing temperature, mixing time and graphitization temperature. The results showed that the graphite for friction material prepared in Example 1.4 performed better in terms of rebound rate and initial oxidation temperature, which indicates that the mixing temperature, mixing time and graphitization temperature selected in Example 1.4 are beneficial to improving the rebound rate and initial oxidation temperature of the graphite for friction material prepared.

[0138] Taking Example 1.4 as a control, the influence of the filler ratio was investigated in Examples 1.6-1.7. The results showed that the graphite for friction material prepared in Example 1.6 performed better in terms of rebound rate and initial oxidation temperature, which indicates that the filler ratio selected in Example 1.6 is beneficial to improving the rebound rate and initial oxidation temperature of the graphite for friction material prepared.

[0139] Taking Example 1.6 as a control, the influence of different carbon materials was investigated in Example 1.8. The results showed that when the coke was replaced with an equal amount of graphite in Example 1.8, the graphite for friction material obtained performed better in terms of rebound rate and initial oxidation temperature. This shows that the use of graphite as the carbon material is beneficial to improving the rebound rate and initial oxidation temperature of the graphite for friction material obtained.

[0140] Taking Example 1.8 as a control, the effects of different organic acids were investigated in Examples 1.9-1.10. The results showed that the graphite for friction material prepared in Example 1.10 performed better in terms of rebound rate and initial oxidation temperature, which indicates that the use of citric acid as an organic acid is beneficial to improving the rebound rate and initial oxidation temperature of the graphite for friction material prepared.

[0141] Example 2 Sodium bicarbonate powder particle size

[0142] Example 2.1

[0143] Different from Example 1.10, the particle size of the sodium bicarbonate powder in Example 2.1 is 150 nm.

[0144] Example 2.2

[0145] Different from Example 1.10, the particle size of the sodium bicarbonate powder in Example 2.2 is 160 nm.

[0146] Example 2.3

[0147] Different from Example 2.1, the particle size of the sodium bicarbonate powder in Example 2.3 is 100 nm.

[0148] Example 2.4

[0149] Different from Example 2.1, the particle size of the sodium bicarbonate powder in Example 2.4 is 200 nm.

[0150] The rebound rate and initial oxidation temperature of the graphite for friction material prepared in Examples 2.1-2.4 were tested, as shown in Table 3.

[0151] Table 3 Performance test data table

[0152]

[0153] It can be seen from Table 3 that, with Example 1.10 as a control, the effect of the particle size of sodium bicarbonate was investigated in Examples 2.1-2.4. It was found that the graphite for friction material prepared in Example 2.1 performed better in terms of rebound rate and initial oxidation temperature, which indicates that the particle size of the sodium bicarbonate powder selected in Example 2.1 is conducive to improving the rebound rate and initial oxidation temperature of the graphite for friction material prepared.

[0154] Example 3 Modified Iron Powder

[0155] Examples 3.1-3.6

[0156] Different from Example 2.1, the modified iron powder in Examples 3.1-3.6 is from Preparation Examples 1.2-1.7 in equal amounts.

[0157] The rebound rate and initial oxidation temperature of the graphite for friction material prepared in Examples 3.1-3.6 were tested, as shown in Table 4.

[0158] Table 4 Performance test data table

[0159]

[0160] It can be seen from Table 4 that, with Example 2.1 as a control, Examples 3.1-3.4 investigated the effect of the ratio of modified iron powder. The results showed that the graphite for friction material prepared in Example 3.1 performed better in terms of rebound rate and initial oxidation temperature, which indicates that the ratio of modified iron powder selected in Example 3.1 is beneficial to improving the rebound rate and initial oxidation temperature of the graphite for friction material prepared.

[0161] Taking Example 3.1 as a control, Example 3.5 replaced sodium polyacrylate with an equal amount of sodium silicate, and Example 3.6 replaced sodium polyacrylate with an equal amount of fumed silica. The rebound rate and initial oxidation temperature of the obtained graphite for friction material were worse than those of Example 3.1. This shows that the use of sodium polyacrylate and iron powder in Example 3.1 is beneficial to improving the rebound rate and initial oxidation temperature of the obtained graphite for friction material.

[0162] Example 4 Sealing agent

[0163] Examples 4.1-4.6

[0164] Different from Example 3.1, the sealing agents in Examples 4.1-4.6 are from Preparation Examples 2.2-2.7 in equal amounts.

[0165] The rebound rate and initial oxidation temperature of the graphite for friction material prepared in Examples 4.1-4.6 were tested, as shown in Table 5.

[0166] Table 5 Performance test data table

[0167]

[0168] It can be seen from Table 5 that, with Example 3.1 as a control, Examples 4.1-4.4 investigated the effect of the sealing agent ratio. The results showed that the graphite for friction material prepared in Example 4.1 performed better in terms of rebound rate and initial oxidation temperature, which indicates that the sealing agent ratio selected in Example 4.1 is beneficial to improving the rebound rate and initial oxidation temperature of the graphite for friction material prepared.

[0169] Taking Example 4.1 as a control, Example 4.5 replaced the graphene aerogel with an equal amount of activated carbon, and Example 4.6 replaced the asphalt-based aluminum paste with an equal amount of silica-aluminum resin. The rebound rate and initial oxidation temperature of the graphite for friction material obtained were worse than those of Example 4.1. This shows that the use of graphene aerogel and asphalt-based aluminum paste in Example 4.1 is beneficial to improving the rebound rate and initial oxidation temperature of the graphite for friction material obtained.

[0170] The volatile matter and sulfur content of the graphite for friction materials prepared in Examples 1 to 4 were tested according to the testing method of the national standard GB / T 3521-2023 "Graphite Chemical Analysis Method". The results show that the volatile matter and sulfur content of the graphite for friction materials prepared in Examples 1 to 4 are all lower than 0.5%, the sulfur content is all lower than 0.5%, and the graphitization degree is between 70 and 90, which meets the use requirements of friction materials.

[0171] Application Example 1

[0172] A friction material is prepared by the following steps:

[0173] The reinforcing fiber, steel fiber, filler, phenolic resin and friction material graphite are mixed evenly, the mixed raw materials are added into a pressing mold, and hot pressing is performed at a hot pressing temperature of 160° C. and a pressure of 30 MPa to obtain the friction material.

[0174] Application Example 2-26

[0175] Different from Application Example 1, the friction material graphite in Application Examples 2-26 is obtained in equal amounts from Examples 1-4.

[0176] Comparative Application Examples 1-3

[0177] Different from Application Example 1, the graphite used for the friction materials in Comparative Application Examples 1-3 is obtained in equal amounts from Comparative Examples 1-3.

[0178] Performance testing experiment

[0179] The following performance test experiments were conducted on the friction materials prepared in Application Examples 1-26 and Comparative Application Examples 1-3. The performance test experiments included shear strength, impact strength, density, wear rate and compression strain rate of the friction materials. The test data are shown in Table 6.

[0180] 1. Shear strength

[0181] The shear strength of the friction material is tested according to the national standard GB / T 22309-2023 "Test method for shear strength of brake linings, disc brake block assemblies and drum brake shoe assemblies for road vehicles". Test temperature: 23±5℃.

[0182] 2. Impact strength

[0183] The shear strength of the friction material is tested according to the national standard GB / T 33835-2017 "Friction Material Impact Strength Test Method". Test temperature: 23±5℃.

[0184] 3. Density

[0185] The density of the friction material is tested according to the test method of the national standard JC / T 685-2009 "Test method for density of friction materials".

[0186] 4. Wear rate

[0187] According to the national standard GB / T 17469-2012 "Test Method for Evaluation of Friction Performance of Automobile Brake Linings", the wear amount of friction material is tested and the wear rate is calculated. Test temperature: 350℃.

[0188] Compression strain rate

[0189] According to the national standard GB / T 22311-2023 "Road Vehicle Brake Lining Compression Strain Test Method", the compression of the friction material is tested and the compression strain rate is calculated. Testing temperature: 400℃.

[0190] Table 6 Performance test data of application example 1-26 and comparative application example 1-3

[0191]

[0192] The following describes the present application in detail in conjunction with the test data provided in Table 6.

[0193] Combining the comparative application examples 1-3 and the application examples 1-26, it is found that the friction materials prepared by the application examples 1-26 of the present application are better than the friction materials prepared by the comparative application examples 1-3 in terms of shear strength, impact strength, wear rate and compression strain rate, and the density is lower than the density of the friction materials prepared by the comparative application examples 1-3, indicating that the graphite used in the friction material of the present application is better in reducing the density, wear rate and compression strain rate of the friction material prepared while improving the shear strength and impact strength of the friction material prepared.

[0194] Combining Application Example 1 and Comparative Application Examples 1-3, it can be found that in Comparative Application Example 1, by replacing the modified iron powder with an equal amount of iron powder, the friction material obtained is inferior to that in Application Example 1 in terms of shear strength, impact strength, density, wear rate and compression strain rate. This shows that the modified iron powder selected in Application Example 1 of the present application is beneficial to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material obtained.

[0195] In comparison with Application Example 2, in which an equal amount of sodium carbonate was used to replace sodium bicarbonate, the friction material obtained performed worse than that in Application Example 1 in terms of shear strength, impact strength, density, wear rate and compression strain rate. This indicates that the sodium bicarbonate selected in Application Example 1 of the present application is beneficial to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material obtained.

[0196] In comparison, in Application Example 3, an equal amount of calcium carbonate was used to replace sodium bicarbonate, and the performance of the friction material obtained in shear strength, impact strength, density, wear rate and compression strain rate were all worse than those in Application Example 1. This shows that the sodium bicarbonate selected in Application Example 1 of the present application is beneficial to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material obtained.

[0197] The effects of the amount of acetic acid and sulfuric acid added were investigated in Application Examples 1-3. The results showed that the friction material prepared in Application Example 2 performed better in shear strength, impact strength, wear rate and compression strain rate, and had a smaller density. This shows that the amount of acetic acid and sulfuric acid added selected in Application Example 2 is more conducive to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material.

[0198] Taking Application Example 2 as a control, the effects of mixing time, mixing temperature and graphitization temperature were investigated in Application Examples 4-5. The results showed that the friction material prepared in Application Example 4 performed better in shear strength, impact strength, wear rate and compression strain rate, and had a smaller density. This shows that the mixing time, mixing temperature and graphitization temperature selected in Application Example 4 are more conducive to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material.

[0199] Taking Application Example 4 as a control, the influence of filler ratio was investigated in Application Examples 6-7. The results showed that the friction material prepared in Application Example 6 performed better in shear strength, impact strength, wear rate and compression strain rate, and had a smaller density. This shows that the filler ratio selected in Application Example 6 is more conducive to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material.

[0200] Using Application Example 6 as a control, the influence of different carbon materials was investigated in Application Example 8. The results showed that when an equal amount of graphite was used to replace coke in Application Example 8, the friction material obtained performed better in shear strength, impact strength, wear rate and compression strain rate, and had a smaller density. This shows that the preferred carbon material of graphite is more conducive to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material.

[0201] Using Application Example 8 as a control, Application Examples 9-10 investigated the effects of different organic acids. The results showed that when citric acid was used to replace acetic acid in Application Example 10, the friction material obtained performed better in shear strength, impact strength, wear rate and compression strain rate, and had a smaller density. This shows that the preferred organic acid of citric acid is more conducive to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material.

[0202] Taking Application Example 10 as a control, the influence of the particle size of sodium bicarbonate was investigated in Application Examples 11-14. The results showed that the friction material prepared in Application Example 11 performed better in shear strength, impact strength, wear rate and compression strain rate, and had a smaller density. This shows that the particle size of sodium bicarbonate selected in Application Example 11 is more conducive to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material.

[0203] Taking Application Example 11 as a control, the influence of the ratio of modified iron powder was investigated in Application Examples 15-18. The results showed that the friction material prepared in Application Example 15 performed better in shear strength, impact strength, wear rate and compression strain rate, and had a smaller density. This shows that the ratio of modified iron powder selected in Application Example 15 is more conducive to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material.

[0204] Taking Application Example 15 as a control, in Application Example 19, an equal amount of sodium silicate was used to replace sodium polyacrylate, and the friction material obtained was worse than that in Application Example 15 in terms of shear strength, impact strength, density, wear rate and compression strain rate; in Application Example 20, an equal amount of fumed silica was used to replace sodium polyacrylate, and the friction material obtained was worse than that in Application Example 15 in terms of shear strength, impact strength, density, wear rate and compression strain rate. This shows that the sodium polyacrylate selected in Application Example 15 of the present application is beneficial to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material obtained.

[0205] Taking Application Example 15 as a control, the influence of the ratio of the sealing agent was investigated in Application Examples 21-24. The results showed that the friction material prepared in Application Example 21 performed better in shear strength, impact strength, wear rate and compression strain rate, and had a smaller density. This shows that the ratio of the sealing agent selected in Application Example 21 is more conducive to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the friction material.

[0206] Taking Application Example 21 as a control, the same amount of activated carbon was used to replace the graphene aerogel in Application Example 25, and the performance of the friction material obtained in shear strength, impact strength, wear rate and compression strain rate were all worse than those in Application Example 21. This shows that the graphene aerogel selected in Application Example 21 of the present application is beneficial to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the obtained friction material.

[0207] Taking Application Example 21 as a control, an equal amount of silicon-aluminum resin was used to replace the asphalt-based aluminum paste in Application Example 26, and the friction material obtained performed worse than those in Application Example 21 in terms of shear strength, impact strength, density, wear rate and compression strain rate. This shows that the asphalt-based aluminum paste selected in Application Example 21 of the present application is beneficial to reducing the density, wear rate and compression strain rate of the friction material while improving the shear strength and impact strength of the obtained friction material.

[0208] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A graphite for friction material, characterized in that: The invention comprises the following raw materials in parts by weight: 10000±20 parts of carbon material, 4900-9900 parts of sulfuric acid, 9900-29700 parts of organic acid, 60-80 parts of filler; The weight ratio of carbon material, organic acid and sulfuric acid is 1: (0.99-2.97): (0.49-0.99); The carbon material is one of a coke-type carbon material or a graphite-type carbon material; The filler comprises 24-28 parts of modified iron powder, 12-14 parts of sodium bicarbonate powder and 30-32 parts of sealing agent; The organic acid is one of acetic acid, oxalic acid or citric acid.

2. The graphite for friction material according to claim 1, characterized in that: The modified iron powder is prepared by wrapping sodium polyacrylate with iron powder, and the weight ratio of the iron powder to sodium polyacrylate is (3-5):

1.

3. The graphite for friction material according to claim 1, characterized in that: The sealing agent is prepared by graphene aerogel adsorbing asphalt-based aluminum paste, and the weight ratio of graphene aerogel to asphalt-based aluminum paste is 1: (10-12).

4. The graphite for friction material according to claim 3, characterized in that: The preparation method of the sealing agent is as follows: Freeze-forming the asphalt-based aluminum slurry to obtain a formed solid; The formed solid is crushed to obtain particles; The graphene aerogel is added to the prepared particles according to a weight ratio and ultrasonically dispersed to prepare a sealing agent.

5. The graphite for friction material according to claim 3, characterized in that: The particle size of the sodium bicarbonate powder is 140-160 nm.

6. A method for preparing graphite for friction material according to any one of claims 1 to 5, characterized in that: The following steps are involved: After mixing the organic acid and sulfuric acid according to the weight ratio, add the carbon material and mix at 40-80°C for 20-60 minutes; Washing the obtained mixture until it is neutral, and drying it to obtain a dried carbon material; The dried carbon material is calcined at 600±10° C. for 12±4 h, and the calcined carbon material is graphitized for 36±1 h to obtain graphitized elastic graphite; Mixing sodium bicarbonate powder and modified iron powder according to weight ratio, adding into graphitized elastic graphite and mixing well to prepare a mixture; The sealing agent is added into the mixture and mixed evenly to obtain graphite for friction material.

7. The method for preparing graphite for friction material according to claim 6, characterized in that: The graphitization temperature is 2000-2800°C.

8. A friction material made of the graphite for friction material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The reinforcing fiber, steel fiber, filler, phenolic resin and friction material graphite are mixed evenly, the mixed raw materials are added into a pressing mold, and hot pressing is performed at a hot pressing temperature of 160±10° C. and a pressure of 30±1 MPa to obtain the friction material.

Citation Information

Patent Citations

  • Friction material composition and friction material

    CN105745298A

  • Negative electrode material of low-temperature lithium battery and preparation method of negative electrode material

    CN106299281A